2000
DOI: 10.1007/bf03028081
|View full text |Cite
|
Sign up to set email alerts
|

The surface morphology of Li metal electrode

Abstract: Surface morphological changes of Li powder compacted electrodes were investigated and compared with extruded Li foil electrodes during the dissolution (discharge)/deposition (charge) process. The area of derlclrite growing surfaces was reduced remarkably for Li powder compacted electrodes. Impedance measurements showed that Li compacted powder electrodes had a lower resistance than Li foil electrodes. This is presumed to be related with resistance reduction due to increasing ion conductivity in the SEI (solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The phase identificationsare marked in the EDPs in (g) and (h). [15] Thestabilized Li powders were compacted and used as the electrode for Li-ion battery, [15] and results show that dendrite growth in the compacted electrode was reduced significantly as compared with an extruded Li foil electrode.I narelated study,i tw as reported that Li 2 CO 3 particles treated graphite electrode showed much better capacity retention, particularly for the first cycle, as compared to the non-treated electrode,because the SEI layer with ah igher Li 2 CO 3 concentration enhanced the stability and assisted Li + diffusion, improving the capacity retention. To test whether the ASLSs can be used as anodes for Li-ion batteries, we constructed an anobattery using an ASLS as an anode, the shell of Li 2 CO 3 and Li 2 Oa sthe electrolyte, and an Au-coated CuO nanowire as the cathode inside the ETEM.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…The phase identificationsare marked in the EDPs in (g) and (h). [15] Thestabilized Li powders were compacted and used as the electrode for Li-ion battery, [15] and results show that dendrite growth in the compacted electrode was reduced significantly as compared with an extruded Li foil electrode.I narelated study,i tw as reported that Li 2 CO 3 particles treated graphite electrode showed much better capacity retention, particularly for the first cycle, as compared to the non-treated electrode,because the SEI layer with ah igher Li 2 CO 3 concentration enhanced the stability and assisted Li + diffusion, improving the capacity retention. To test whether the ASLSs can be used as anodes for Li-ion batteries, we constructed an anobattery using an ASLS as an anode, the shell of Li 2 CO 3 and Li 2 Oa sthe electrolyte, and an Au-coated CuO nanowire as the cathode inside the ETEM.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This result confirms that ASLSs are aversatile anode material for lithium batteries.T he structure of the ASLSs is similar to the surface-stabilized Li powders produced by the droplet emulsion technique (DET), which also exhibit aLi 2 CO 3 shell and aLicore. [15] Thestabilized Li powders were compacted and used as the electrode for Li-ion battery, [15] and results show that dendrite growth in the compacted electrode was reduced significantly as compared with an extruded Li foil electrode.I narelated study,i tw as reported that Li 2 CO 3 particles treated graphite electrode showed much better capacity retention, particularly for the first cycle, as compared to the non-treated electrode,because the SEI layer with ah igher Li 2 CO 3 concentration enhanced the stability and assisted Li + diffusion, improving the capacity retention. [16] Remarkably,A sadi and co-workers recently reported ar ecord-long cycle lifetime of 700 cycles for aL iair battery by using aL i 2 CO 3 -protected Li foil as the anode and cycling in asimulated air atmosphere.They attributed the record-long cycle lifetime to the presence of aL i 2 CO 3 passivation layer on the Li surface,w hich protects the metallic Li from corrosion by the moisture,C O 2 ,a nd O 2 in an air-like atmosphere.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Unfortunately, the commercialization of lithium-metal cells is limited by various factors, such as dendrite growth, an unstable solid–electrolyte interphase (SEI), and capacity fading. Electrolyte additives, ex situ artificial layers, and composite anodes have been tested to suppress Li dendrite growth and stabilize the SEI. In addition, Li powder has been demonstrated to be effective in suppressing dendrite growth, forming a stable SEI and a stable interface shape and area, according to data that have been reported in the last few decades. , …”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [21] introduced the droplet emulsion technique (DET) for synthesis of lithium powder (Li p ) that was used for the preparation of compact Li p electrodes. In comparison with Li foil electrodes, the Li p electrodes demonstrated lower impedance and reduced HSAL formation after Li electrodeposition/electrodissolution processes.…”
Section: Introductionmentioning
confidence: 99%
“…The improved performance was attributed to the higher ionic conductivity of the solidÀelectrolyte interphase (SEI) [22] formed on such Li p particles and the larger surface area of the Li p electrodes that lead to lower local current densities and thus suppressed HSAL formation. [21] Based on the work of Kim et al, [21] further studies focused on the synthesis of surface-coated Li p , [23] where improved performance of Li p electrodes was achieved by the application of a higher compression degree, [24] the preparation of composite Li p electrodes using Cu powder, [25] and by chemical modification of the Li p particles in Li p electrodes using a cementation reaction with ZnI 2 . [26] Although the DET method was described in regard to the processing steps, [23,27,28] little work has been focused on deciphering the effect that various parameters within the DET method have on the particle size, shape, and interfacial properties of the synthesized Li p particles.…”
Section: Introductionmentioning
confidence: 99%